Laser-flash-photolysis-spectroscopy: a nondestructive method?. (8th February 2017) - Schneider, Jenny; Nikitin, Konstantin; Dillert, Ralf; Bahnemann, Detlef W.
Abstract : Herein, we report the effect of the laser illumination during the diffuse-reflectance laser-flash-photolysis measurements on the morphological and optical properties of TiO2 powders. A grey-blue coloration of the TiO2 nanoparticles has been observed after intense laser illumination. This is explained by the formation of nonreactive trapped electrons accompanied by the release of oxygen atoms from the TiO2 matrix as detected by means of UV-vis and EPR spectroscopy. Moreover, in the case of the pure anatase sample a phase transition of some TiO2 nanoparticles located in the inner region from anatase to rutile occurred. It is suggested that these structural changes in TiO2 are caused by an energy and charge transfer to the TiO2 lattice.